Zeven hoofdzonden en een paar deugden Theologische inzichten voor het alledaagse leven - Sterkens, Carl; Hübenthal, Christoph (Radboud University Press, 2023)
In our modern secular society, theology is capturing progressively less attention and is being granted minimal importance within the wider community. Unjustly so, as this collection of essays demonstrates. On the occasion of the centenary of Radboud University (1923-2023), researchers and professors from the Faculty of Theology present a series of easily comprehensible theological insights concerning both human frailties and the greatness of humanity. Using the deadly sins and a few virtues as a guiding framework, these essays explore lighthearted the boundaries, horizons, and ambiguities of human existence. This volume combines perspectives from Biblical studies, church history, systematic theology, and practical theology to address individual challenges and societal discussions. The seven deadly sins provide food for thought on what can go wrong in individual lives and in society. The classic list of pride (superbia), greed (avaritia), envy (invidia), lust (luxuria), gluttony (gula), wrath (ira), and sluggishness (acedia) still affect us. Virtues, on the other hand, are often less actively pursued, yet they inspire us to critically observe our surroundings: love (caritas), justice (iustitia), and fairness (aequitas). These insights often draw from the rich history of Nijmegen's Faculty of Theology. Not to imply that its approach is a unique breeding ground for vices, but rather to acknowledge the joyous occasion that spurred this collection. The compilation wraps up with art-historical reflections on the images that eloquently enhance the contributions.